Structural imbalance and integrated economic development of RCEP countries on perspective of industrial network - Yin, Chong; Su, Xiao-ni; Wang, Wen-chao; Cui, Ying-xin (Technological forecasting & social change, 2024)
In the decade of the RCEP negotiations, structural changes and imbalance have occurred in the regional economic system. For this problem, the paper analyzed structural imbalance and its impacts on integrated economic development of the RCEP countries and India from perspective of industrial network. We designed structural indicators describing imbalance of industrial system and impact of imbalance on integrated development. Empirical analysis was based on the world input-output data for 2010, 2015 and 2019. It can be found that economic imbalance reflected in China's dominant role, structural deviation, weak and excessive stability, hierarchy. So RCEP region is integrated relying on three heterogeneous economic blocks, including the power center, affiliated members, and sub centers and their partners, which produce centripetal integration, segmentation and decentralization effects. This imbalance is a double-edged sword for regional integration, and the adaptability and flexibility of the structure are key. Further, some implications were given for promoting strategic economic path of related countries and improving the RCEP protocol. •Structural imbalance and its impacts on integrated economic development of RCEP countries are revealed on industry networks.•Structural indicators describing imbalance of industrial systems and its impact on integrated development are designed.•Economic imbalance of RCEP region is reflected in structural deviation and instability. Integration of RCEP region relies on heterogeneous blocks producing centripetal, segmentation and decentralization effects.•We gave advice on improving RCEP protocol and economic reform of related countries.